Managing Pesticides for Greener Growth in Lao PDR : Policy Note - World Bank (World Bank, Vientiane, 2021)
Sound pesticides management and Integrated Pest Management (IPM) in particular are widely acknowledged as important mechanisms to mitigate pre- and post-harvest losses and to achieve sustainable agricultural intensification. The recent proliferation of agricultural concessions, contract farming arrangements, subsidies and other mechanisms in the country to stimulate production also mean a facilitated access to inputs that must be regulated. Preserving Lao PDR’s rich biodiversity is not only a conservation goal in itself but also contributes to food security, poverty reduction and development. Sound pesticides management contributes to agricultural competitiveness and trade. Trade in agricultural products, and in particular market access, is affected by the presence of pests in a traded consignment or the presence of excessive pesticide residues in food products that attract the application of sanitary and phytosanitary (SPS) measures by trading partners. The Lao PDR Government has made strides in controlling banned, unregistered and illegally imported pesticides in the last ten years.